HERBICIDAL COMPOSITION AND ITS USE - OTSUKA TAKASHI; HACHITANI YOICHI; ODA YOSHIKI; NISHIOKA HITOSHI (1999)
PROBLEM TO BE SOLVED: To obtain the subject composition that manifests effective combating activity against weeds that are important in the cultivation of rice plant by using 3-substituted phenyl pyrazole derivative, (RS)-bromo-N-(α,α- dimethylbenzyl)-3,3-dimethylbutyl amide (compound a) and 2-[2-(3- chlorophenyl)-2,3-epoxypropyl]-2-ethylindiane-1,3-dione (compound b). SOLUTION: This herbicidal composition is obtained by using (A) a 3- substituted phenylpyrazole derivative of the formula [R is COOR (R is a 1-6C alkyl); R is a 1-6C alkyl; R is H; X1 and X are each a halogen; Y is O; n is 0, 1], (B) the compound a and (C) the compound b in which the total of the components A, B and C is 3-50 pts.wt. per 100 pts.wt. of the composition and the weight ratio of the component A: the component B: the component C is preferably 1:(1-100):(5-20).